Use of New Media as a Tool of Public Relations: The Delhi Traffic Police Case Study - Bhattacharjee, Tomojit (Journal of Advanced Research in Journalism & Mass Communication, 2018)
The Delhi Traffic Police is one of the largest traffic police forces in India. Managing traffic in a city teeming with vehicles is a massive challenge and transparent communication is extremely important to convey to people all the important information pertaining to the flow of traffic in the city. Therefore, the Delhi Traffic Police was one of the India’s first government organizations to implement new media tools in its communication strategy. The police force introduced a website, social media channels in Facebook, Twitter besides also starting helpline services on WhatsApp. This study endeavored to find how effective has been the implementation of these new media tools. Content analysis of the leading newspapers as well as the study of the social media channels of the organization revealed that the adoption of new media has resulted in enhancement of the public image of the organization. How to cite this article: Bhattacharjee T. Use of New Media as a Tool of Public Relations: The Delhi Traffic Police Case Study. J Adv Res Jour Mass Comm 2018; 5(3): 26-32. DOI: https://doi.org/10.24321/2395.3810.201811